(untitled) (International Journal of Creative Future and Heritage (TENIAT), 2025)
ABSTRACT Soft power has become increasingly important in understanding a country’s ability to influence and attract others beyond its military and economic capabilities. South Korea has become a significant player mainly because of its thriving entertainment industry. The television series Squid Game (2021) exemplifies this trend, gaining global recognition and serving as a testament to South Korea’s cultural influence. This study investigated the role of the Squid Game in enhancing South Korea’s soft power through its viewership and popularity, international awards and recognition, cultural influence, and economic impact. By examining these factors, this study provides a comprehensive understanding of how the Squid Game has contributed to South Korea’s global presence and solidified its position in the realm of soft power. The methodology involved a comprehensive literature review and content analysis of secondary sources, including academic journals, news articles, and media reports. Findings highlight Squid Game’s ability to captivate international audiences, spark cultural dialogues, and drive economic benefits, showcasing South Korea’s cultural prowess and increasing influence on the global stage. Future recommendations include further research on the long-term impacts of cultural exports on soft power and exploring similar phenomena in other cultural contexts. ABSTRAK Kuasa lembut semakin penting dalam memahami keupayaan sesebuah negara untuk mempengaruhi dan menarik minat pihak lain selain daripada keupayaan ketenteraan dan ekonominya. Korea Selatan telah menjadi pemain utama terutamanya disebabkan oleh industri hiburannya yang berkembang pesat. Siri televisyen Squid Game (2021) merupakan contoh jelas trend ini, memperoleh pengiktirafan global dan menjadi bukti pengaruh budaya Korea Selatan. Kajian ini meneliti peranan Squid Game dalam meningkatkan kuasa lembut Korea Selatan melalui jumlah penonton dan populariti, anugerah dan pengiktirafan antarabangsa, pengaruh budaya, dan kesan ekonomi. Dengan meneliti faktor-faktor ini, kajian ini memberikan pemahaman yang menyeluruh tentang bagaimana Squid Game menyumbang kepada kehadiran global Korea Selatan dan mengukuhkan kedudukannya dalam bidang kuasa lembut. Metodologi kajian ini melibatkan kajian literatur yang komprehensif dan analisis kandungan sumber sekunder, termasuk jurnal akademik, artikel berita, dan laporan media. Hasil kajian menonjolkan keupayaan Squid Game untuk memikat penonton antarabangsa, mencetuskan dialog budaya, dan menghasilkan manfaat ekonomi, yang sekaligus menunjukkan kehebatan budaya Korea Selatan dan pengaruhnya yang semakin meningkat di peringkat global. Cadangan untuk kajian masa depan termasuk kajian lanjut mengenai kesan jangka panjang eksport budaya terhadap kuasa lembut serta meneroka fenomena serupa dalam konteks budaya yang lain.